Analysis of techniques of raising questions of teachers to evolve student thinking skill leading to improve student achievement - Husnawati Husnawati; Muhibbuddin Muhibbuddin; Abdullah Abdullah (Universitas Syiah Kuala, 2014)
The study was aimed to determine the description and classification of questions, distribution of questions raised by teachers, capability of teachers and the techniques, and the effect of the techniques on student achievement. The method was quantitative descriptive. The data was collected from 1 st April to 30th 2013 in 14 junior high schools in Banda Aceh throught pretest and posttest . Moreover, teachers were given sheets of observation of questioning teachnique, records of teaching learning activity, and questionare. Data was analysed descriptivelly and by using regretion-correlation analysis. The results showed that in terms of knowlegde aspect, only 25,53 % of the total teachers had skill to evolve student thinking skill, 2,16 % (cognitive aspect), and 4,32 % (scientific psychomotoric skill). Furthermore, it has been found that the questions were not spread evenly and only 53,33 % of the total teachers had the capability in improving student thinking skill throught questions. The techniques were probing (13,33 %) and redirecting (86,67 %). Moreover, the persentage of total teachers who have raised questions in good criteria was 13,33 and only 1,48 % of the total teachers who had the technique contributing in improvement of student achievement (less correlation).